Software engineering - Sommerville, Ian (Boston : Pearson Education Limited, 2016)
"This book introduces students to the overwhelmingly important subject of software programming and development. In the past few years, computer systems have come to dominate not just our technological growth, but the foundations of our world's major industries. This text seeks to lay out the fundamental concepts of this huge and continually growing subject area in a clear and comprehensive manner." -- Provided by publisher
Includes bibliographical references and index
1 4 10
Keywords: Software engineering; Software engineering -- Handbooks, manuals, etc; Textbooks -- Bibliography